LAPORAN KEUANGAN BERBASIS STANDAR AKUNTANSI KEUANGAN PADA BADAN LAYANAN UMUM DAERAH DI LINGKUNGAN DINAS KOPERASI DAN UMKM PEMERINTAH PROPINSI JAWA TIMUR - Lestari, Yona Octiani (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2012)
ABSTRACT Indonesian government has established a microcredit plan for Union or Koperasi and UMKM, which goes by abbreviation: KUMKM. This microcredit plan requires benefited Koperasi and UMKM to give periodical financial report based on Indonesian general financial accounting standard as a proof of progression. This seems to be major factor of current microcredit plan. BPS added value survey in 2008 showed that 98% KUMKM in Indonesia seems to independently support themselves. The report indicates that KUMKM could face structural difficulties in obtaining capital assistance and other financial aids due to their incapability of making appropriate financial report. In order to further assist potential KUMKM, Regional Public Service Agencies (BLUD) should implement detailed financial report system based on general financial accounting standards. Furthermore, recognitions and measurements all accounts must comply with rules governing the Financial Accounting Standards Board